2022
DOI: 10.29267/mxjb.2022.7.4.14
|View full text |Cite
|
Sign up to set email alerts
|

Molecular interaction of linear and branched fructans of different sizes with levansucrase and inulosucrase from Lactobacillus gasseri: modeling and computational analysis

Abstract: Human beings consume probiotics and prebiotics because of the health benefits they provide. Lactobacillus gasseri is a probiotic microorganism native to humans which produces glycolytic enzymes directed at the hydrolysis of soluble fibers as prebiotic fructans. In this work, levansucrase (LevG) and inulosucrase (InuGB) from L. gasseri were used to predict the ability of L. gasseri to interact with linear and branched fructans prebiotics (inulin and agavins). AlphaFold and SWISS-MODEL were the servers used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…; these are responsible for the hydrolysis of fructans, which could depend on the structure and chain size of fructans. For example, Marti ́nez-Peŕez and Moreno-Vilet 43 reported that levansucrase and inulosucrase of L. gasteri have a better affinity to agavin or branched structures and inulin or linear structures, respectively, as obtained by the molecular docking study. Besides, better affinity energies were obtained with DPs 6 and 8 linked fructose unit chain sizes, as confirmed by us in this study with fructans with low DPs.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%
“…; these are responsible for the hydrolysis of fructans, which could depend on the structure and chain size of fructans. For example, Marti ́nez-Peŕez and Moreno-Vilet 43 reported that levansucrase and inulosucrase of L. gasteri have a better affinity to agavin or branched structures and inulin or linear structures, respectively, as obtained by the molecular docking study. Besides, better affinity energies were obtained with DPs 6 and 8 linked fructose unit chain sizes, as confirmed by us in this study with fructans with low DPs.…”
Section: ■ Materials and Methodsmentioning
confidence: 91%